Periodontal health of renal patients and quality of life associated. Exploratory study - Betancur-Quintero, Steven (2020)
Objective. Determine the periodontal health status of the renal transplantation patient, by reviewing the medical records filled out by general dentists or specialists as well as the perception of post-transplantation quality of life, in relation to oral health. Methods. Cross-sectional descriptive study with 30 participants from renal transplantation unit in the city of Medellín, Colombia. Personal and family medical-dental history, oral exam and complete periodontogram were explored by a single examiner (Kappa = 0.79). The Oral Health Impact Profile (OHIP-14) survey was applied. Results. Average age: 35 years (d.s ± 20.5), 50% men and 70% residents in Medellín. 46.7% had idiopathic renal failure. From the 44.3% who presented periodontal problems, 73% had localized periodontitis, 31.8% periodontal pockets of 4 mm. The quality of life applied questionnaire showed two affected dimensions: physical pain and psychological distress (23.4% and 20% respectively). Conclusions. The kidney transplantation patients had periodontal involvement. The severity measured by the loss of insertion, showed an unsatisfactory result, considering that patients should be free of irritating and inflammatory factors in the mouth. The OHIP-14 is a friendly and simple instrument to assess the quality of life associated with oral health.